Microbiome and metabolome reveal beneficial effects of baicalin on broiler growth performance and intestinal health - Xingbo Liu; Yunru Ji; Huiyuan Lv; Zengpeng Lv; Yuming Guo; Wei Nie (Poultry Science)
Normal function and health of the intestinal tract were necessary for the growth and development of broilers. Baicalin (BA) possessed a variety of biological activities. The objective of this study was to examine the impact of BA on the growth performance, intestinal barrier function, intestinal microbiota, and mucosal metabolism in broilers. A total of 720 21-day-old broilers were randomly allocated into 3 groups and fed with either basal diet (Con group) or basal diet supplemented with 6 or 12 mg/kg baicalin (BA6 and BA12 groups) for a continuous feeding period of 40 days. Results showed that BA had a trend towards improving (P = 0.086) the 60-day body weight of broilers, and the BA12 group exhibited significantly higher (P < 0.05) average daily gain from day 39 to 60 compared to the Con group. Additionally, in the BA12 group, the ratio of villus height to crypt depth and the expression levels of tight junction protein-related genes significantly increased (P < 0.05), while intestinal permeability significantly decreased (P < 0.05). Supplementation with 12 mg/kg BA significantly enhanced antioxidant capacity, promoted (P < 0.05) crypt proliferation, increased (P < 0.05) immunoglobulin levels, upregulated (P < 0.05) IL-2 and IL-8 mRNA levels, and downregulated (P < 0.05) IL-4 and TGF-β2 mRNA levels. Metabolomics analysis revealed that BA improved the metabolic characteristics of intestinal mucosa, significantly upregulating pathways associated with ascorbate and aldarate metabolism, glyoxylate and dicarboxylate metabolism, phosphatidylinositol signaling system, alpha-linolenic acid metabolism, and galactose metabolism. 16S rRNA sequencing results indicated that BA increased the richness of intestinal microbiota community and the relative abundance of Actinobacteria phylum, while reducing the relative abundance of contains mobile elements, potentially pathogenic, and facultatively anaerobic. Overall, 12 mg/kg BA improved intestinal health by modulating intestinal barrier function, antioxidant capacity, immunity, intestinal microbiota, and intestinal mucosal metabolism levels, ultimately enhancing broiler growth performance.